The Implementation of Reward Techniques and their Effectiveness to Attract Students in Learning Malay Language during Learning and Teaching at Home (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
This study was conducted to see the types of reward techniques that have been used by teachers and their effectiveness to attract students’ interest in learning Malay language during teaching and learning at home (PdPR). A total of 90 primary school teachers teaching Malay language were involved in this study. All the teachers come from two districts in Sarawak. This quantitative study uses a survey study design. A questionnaire was distributed through Google Forms to collect the data. The findings are explained descriptively to report its frequency, mean, standard deviation, and percentage. The results of the analysis showed that the primary school teachers of Malay language mainly used the physical and social reward techniques during PdPR based on the highest mean value. From the reaction of the students towards the rewards, it is found that the teachers of Malay language mainly used emotional, cognitive and social reactions to increase the interest of students while learning Malay language during PdPR. Similarly, giving rewards impacted the interest and grades of the students when learning Malay language during PdPR. The implication of this study is that reward techniques can increase the interest of students to learn even though the learning occurs online. In summary, Malay language teachers can use reward techniques as an effective online teaching and learning method (PdP) to teach students at home.Full text: PDF